Where am I? Who am I? The Relation Between Spatial Cognition, Social Cognition and Individual Differences in the Built Environment - Proulx, Michael J.; Todorov, Orlin S.; Taylor Aiken, Amanda; de Sousa, Alexandra A. (Frontiers in Psychology, 2016)
Knowing who we are, and where we are, are two fundamental aspects of our physical and mental experience. Although the domains of spatial and social cognition are often studied independently, a few recent areas of scholarship have explored the interactions of place and self. This fits in with increasing evidence for embodied theories of cognition, where mental processes are grounded in action and perception. Who we are might be integrated with where we are, and impact how we move through space. Individuals vary in personality, navigational strategies, and numerous cognitive and social competencies. Here we review the relation between social and spatial spheres of existence in the realms of philosophical considerations, neural and psychological representations, and evolutionary context, and how we might use the built environment to suit who we are, or how it creates who we are. In particular we investigate how two spatial reference frames, egocentric and allocentric, might transcend into the social realm. We then speculate on how environments may interact with spatial cognition. Finally, we suggest how a framework encompassing spatial and social cognition might be taken in consideration by architects and urban planners.